(untitled) - Jordan, Emma Coleman (New York, N.Y., 2005)
Economic Justice: Race, Gender, Identity and Economics is a new casebook, offered as a means to further the conversation between critical legal scholarship and law and economics. The phrase “economic justice” signals the authors’ aim to engage these two cultures, and to find the answer to questions, such as: What can economics tell us about democracy and the law? What can theories of justice tell us about economic theory and the law?
Keywords: Law,Economics,Law and economics,Luật pháp; Economic aspects, Moral and ethical aspects,Khía cạnh kinh tế; United States,United States,Hoa Kỳ